Fostering creative thinking skill among building technology students of technical colleges in Nigeria - Ojo, Oke Jonathan (2016)
Creativity is needed in schools to develop students’ innovative ideas. However, the Federal Government of Nigeria has not been able to integrate creative thinking skill into the Building Technology curriculum of technical colleges as enshrined in the National Policy on Education due to lack of model to foster the skill. This study therefore was aimed at developing two models for fostering creative thinking skill among the Building Technology students in Nigeria technical colleges based on teachers and students’ perception. The design of the study was an explanatory sequential mixed method. The quantitative aspect of the design utilized questionnaire for data collection; while the qualitative aspect utilized interview protocol in collecting data from its participants. The quantitative research purposively made use of 215 Building Technology teachers/ experts/ principals and 638 Building Technology students proportionally sampled from all the technical colleges offering Building Technology in the South-West Geopolitical Zone of Nigeria. The qualitative research also purposively involved 14 participants for interview either through direct contact or the use of Social Media. In addition, direct observation technique was carried out on six students during preliminary study to elicit the process involved in creative thinking skill. Data collected in quantitative research were analysed using Statistical Package for Social Science (IBM SPSS version 21.0) and Analysis of Moment Structures (AMOS version 18). Data were analysed with percentages, mean, standard deviation and ttest. On the qualitative aspect of the research, content analysis was used. The major findings of the study showed that creative thinking skill can be fostered in Nigeria technical colleges with due consideration for: background information that will warrant students selection; necessary social environmental factors; the required resources; the required creative thinking skill teaching techniques; the motivational techniques; the creative thinking skill process as well as the expected creative thinking skill. Two measurement models were developed using maximum likelihood. Therefore, the models fulfilled the threshold values of Modification Indices such as absolute fit, incremental fit and parsimonious fit. The values obtained also confirmed the validity and reliability of the models across the samples. The developed models were therefore recommended for the use of the Federal Government of Nigeria, the curriculum planners and building technology teachers as guide for fostering creative thinking skill in Nigeria technical colleges.